Structure and force generation capacity on knee extension and flexion muscles in amatuer junior wrestlers - Hiratsuka, K.; Ihara, Y.; Teshima, T.; Tanaka, S.; Kumagawa, D.; Tsunoda, N. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Structural and functional characteristics of the skeletal muscle are directly affect to the athletic performance in amateur wrestlers. It is cleared that the characteristics of muscle structure and force generation capacity due to body size are important to planning for the training program. Therefore, the purpose of this study was to investigate characteristics of the muscle structure and function with body weight class in Japanese amateur junior wrestlers. Methods: The subjects were 29 Japanese amateur junior wrestlers aged from 16 to 17 years old. These subjects were classified light body weight (<64kg: LG), middle body weight (65-75kg: MG) and heavy body weight (76kg<: HG). The whole and lower limb muscle volumes were measured by the body impedance analysis methods. Moreover, the relative value of lower limb muscle volume to the whole muscle volume was calculated in all the subjects. Isokinetic peak torques on knee extension and flexion as a muscle functional parameters were measured using isokinetic dynamometer (Biodex System 3). And also, isokinetic knee extension and flexion torques measurement with 30 repetitive maximal contractions as a muscle endurance index was measured in all the subjects. Results: Significant differences of whole and lower limb muscle volume were obtained among the three groups. In HG, relative lower limb muscle volume to the whole muscle volume was significantly higher than that of LG and MG. The knee extension and flexion peak torques to the body weight in MG were showed highest value compared to the other groups. Significant difference of decrease ratio on knee extension with 30 repetitive maximal contractions was not observed among the three groups. However, significant group difference was observed in knee flexion contractions. Discussion: The relative lower limb muscle volume to the whole muscle volume in HG showed higher than that of MG and LG. Muscle force generation capacities related to the peak torque of knee flexion in MG was significantly decreased compared to the other groups. From the results in this study, it seems that the states of the muscle size and function in amateur junior wrestlers are important factor for the planning of the fitness training program.